2022
DOI: 10.1080/21655979.2022.2051785
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity associated (FTO)-mediated N6-methyladenosine modification of Krüppel-like factor 3 (KLF3) promotes osteosarcoma progression

Abstract: ARSTRACT N6-methyladenosine (m6A) methylation is the most common and abundant methylation modification of eukaryotic mRNAs, which is involved in tumor initiation and progression. The study aims to explore the potential role and the regulatory mechanism of fat mass and obesity associated (FTO) in osteosarcoma (OS) progression. In this study, we detected the expressions of Krüppel-like factor 3 (KLF3) in OS cells and tissues and found that the mRNA and protein levels of KLF3 were increased in OS cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Numerous significant signal pathways, including NF‐kB, Notch, Wnt, TGF‐β and Runx2, can be impacted by the imbalance of KLFs 21–24 . Moreover, KLFs may also be employed as noncoding RNAs (ncRNAs) target genes to regulate OS cell proliferation, invasion and migration 25,26 . Here, we highlight the role of KLFs in bone diseases and discuss the shared molecular mechanism between them by analysing previously published findings.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Numerous significant signal pathways, including NF‐kB, Notch, Wnt, TGF‐β and Runx2, can be impacted by the imbalance of KLFs 21–24 . Moreover, KLFs may also be employed as noncoding RNAs (ncRNAs) target genes to regulate OS cell proliferation, invasion and migration 25,26 . Here, we highlight the role of KLFs in bone diseases and discuss the shared molecular mechanism between them by analysing previously published findings.…”
Section: Introductionmentioning
confidence: 92%
“…26,205 Overexpression of KLF3 up-regulates p21 in OS cells and counteracts the rise in Cyclin D1 expression mediated by RNA demethylase (FTO), which prevents OS cells from proliferating and invading and instead encourages apoptosis. 26 Interestingly, KLF6 also inhibits OS by affecting the cell cycle. Zhu et al 206 found that overexpression of KLF6 up-regulated the expression of p21 in MG63 cells (human OS cells) while decreasing the expression of bcl-2 and MMP-9.…”
Section: Klfs and Os Proliferation Migration And Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…KLFs indirectly affect EMT in cancer tissues by regulating MMP9, TWIST, and other factors or interacting with TGF-β, WNT, and other pathways. Overexpression of KLF3 abrogates fat mass and obesity-associated-induced osteosarcoma cell invasion ( 155 ) while silencing this factor promotes EMT and metastasis in lung cancer. KLF4 has a reciprocal regulatory relationship with TGF-β1 and thus affects EMT ( 84 , 87 ).…”
Section: Implications Of Klfs In Tumor Developmentmentioning
confidence: 99%
“…RNA modifications also play a role in osteosarcoma metastasis. The m6A demethylase FTO mediates mRNA demethylation, promoting the decay of KLF3 mRNA and decreasing its expression, consequently facilitating osteosarcoma proliferation and metastasis ( 14 ). Also, the destabilizing effects of FTO on DACT1 mRNA promotes Wnt signaling and consequently osteosarcoma metastasis ( 15 ).…”
Section: Introductionmentioning
confidence: 99%